Making Time for Critique: Canadian ‘Right to Shelter’ Debates in a Chrono-Political Frame - Zion, Mark (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2020)
This article engages with Canadian ‘right to shelter’ discourse, with a focus on shared assumptions that do crucial work but are sometimes unstated. It offers a ‘chrono-political’ framework to organize various claims made in the courtroom, in legal academic commentary, and by homeless people themselves. People sleeping outdoors have had noteworthy success in court, preventing immediate bodily peril. However, the ‘emergency’ temporality in those cases ultimately offers a limited politics. The author evaluates proposals from legal academics who therefore prescribe court orders that aim to transcend emergency protection: the state ought proactively to provide some minimal level of shelter to everyone, thereby conjoining the emergency temporality with a longer term ‘progressive’ temporality. However, it is argued that these proposals insufficiently formulate how judges understand their institutional role and the extent to which courtroom doctrine can redirect wider neoliberal trends. Regulative assumptions about ‘gradual improvement’ in the law must themselves be interrogated. As an antipode for the courtroom emergency temporality, a ‘dissensual’ temporality is explored, not as a ‘solution,’ but as an already operant politics, one not previously explored in legal academic commentary on the ‘right to shelter.’ Never to be romanticized, the tent city is nonetheless seen to enact what Jacques Rancière terms ‘dissensus,’ in which participants stage their equality in a way that calls into question the existing arrangement of political intelligibility. Amidst present constraints, dissensus discloses an expansive nonlinear temporality that channels egalitarian predecessors, taking feasible action in the present and attempting to prefigure a more equal future dwelling arrangement.